Pengabdian Masyarakat Donor Darah dan Pemeriksaan IVA Masyarakat Peringatan Hari Bakti Dokter Indonesia ke-119 dan HUT IDI ke-72 “Berbakti Untuk Negri Mengabdi Untuk Rakyat” - Lestari, Hesti; Rinaldi, Enrico Adhitya (Universitas Muhammadiyah Prof. DR. Hamka (UHAMKA Press), 2024)
Blood donation is a process of taking a certain percentage of the blood we have. There is a lot of good that an individual can gain if that individual gives their blood to another individual who needs it, provided that the individual donating blood must comply with the specified donor requirements. This community service is carried out with one of the objectives, namely to provide empowerment for the wider community. Apart from commemorating the 119th Indonesian Doctor's Service Day and also the 72nd IDI Anniversary, this activity was carried out as a form of solidarity between people to help each other in the health sector. Community service activities were carried out from May to November 2023, blood donation activities and VIA examinations were carried out on different dates. Participants who participated in this activity included many parties. From the recorded data, the total number of participants who took part in this activity was 538 participants, with details of 468 participants who participated in blood donation and 70 participants who took part in VIA examinations. Overall, community service activities commemorating the 119th Indonesian Doctor's Service Day and also the 72nd IDI Anniversary ran smoothly.